Towards understanding the effects of individual gamification elements on intrinsic motivation and performance. (June 2017) - Mekler, Elisa D.; Brühlmann, Florian; Tuch, Alexandre N.; Opwis, Klaus
Abstract: Research on the effectiveness of gamification has proliferated over the last few years, but the underlying motivational mechanisms have only recently become object of empirical research. It has been suggested that when perceived as informational, gamification elements, such as points, levels and leaderboards, may afford feelings of competence and hence enhance intrinsic motivation and promote performance gains. We conducted a 2 × 4 online experiment that systematically examined how points, leaderboards and levels, as well as participants' goal causality orientation influence intrinsic motivation, competence and performance (tag quantity and quality) in an image annotation task. Compared to a control condition, game elements did not significantly affect competence or intrinsic motivation, irrespective of participants' causality orientation. However, participants' performance did not mirror their intrinsic motivation, as points, and especially levels and leaderboard led to a significantly higher amount of tags generated compared to the control group. These findings suggest that in this particular study context, points, levels and leaderboards functioned as extrinsic incentives, effective only for promoting performance quantity. Highlights: We experimentally studied the effects of individual game elements on motivation and performance. Gamification increased the number of tags in an image annotation task. Gamification did not affect intrinsic motivation or competence need satisfaction. Lack of motivational effects likely due to the way gamification was implemented. Results suggest that in the given context game elements acted as extrinsic incentives.